2016
DOI: 10.18632/oncotarget.9827
|View full text |Cite
|
Sign up to set email alerts
|

ATG4A promotes tumor metastasis by inducing the epithelial-mesenchymal transition and stem-like properties in gastric cells

Abstract: The metastasis of tumor cells to distant organs is an ominous feature of gastric cancer. However, the molecular mechanisms underlying the invasion and metastasis of gastric cancer cells remain elusive. In this study, we found that the expression of ATG4A, an autophagy-regulating molecule, was significantly increased in gastric cancer tissues and was significantlycorrelated with the gastric cancer differentiation degree, tumor invasion and lymph node metastasis. ATG4A over-expression significantly promoted gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 52 publications
1
28
0
Order By: Relevance
“…Several works show that defects in the autophagic machinery restrain dissemination and metastatic spreading of cancer [20][21][22]. In line with these facts, inhibition of autophagy reduces FSTL1 (follistatin like 1)-induced EMT in human bronchial epithelial cells [23], whereas ATG4A overexpression significantly promotes EMT in gastric cancer cells [24]. Conversely, there is evidence indicating that autophagy acts to prevent EMT and that the activation of the autophagic machinery may determine reversion of the EMT phenotype in cancer cells [25][26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 76%
“…Several works show that defects in the autophagic machinery restrain dissemination and metastatic spreading of cancer [20][21][22]. In line with these facts, inhibition of autophagy reduces FSTL1 (follistatin like 1)-induced EMT in human bronchial epithelial cells [23], whereas ATG4A overexpression significantly promotes EMT in gastric cancer cells [24]. Conversely, there is evidence indicating that autophagy acts to prevent EMT and that the activation of the autophagic machinery may determine reversion of the EMT phenotype in cancer cells [25][26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 76%
“…It was hypothesized that overexpression of the regulator of G-protein signaling pathway 1 (RGS1) might promote the transition of stem cells into CSCs [308]. Besides, CSCs are involved in EMT progression via a vast number of mechanisms, including an overactivation of KRAS, STAT3, Rac1, Wnt, Notch, PTEN, ERK, NF-κB signaling pathways, or hypoxic microenvironment [309][310][311][312][313][314][315][316][317][318]. Recently, researchers have proposed the role of CSC-associated protein, leucine-rich repeat and immunoglobulin-like domain-containing nogo receptor-interacting protein 2 (LINGO2), in gastric cancer and EMT initiation [319].…”
Section: Stem Cellsmentioning
confidence: 99%
“…Some literatures investigate the relationship between autophagy and EMTs using tumor cell lines in pancreatic cancer, cholangiocarcinoma, hepatocellular carcinoma, gastric cancer, glioblastoma, and so on. Yang et al demonstrated that ATG4A promotes the metastasis of gastric cancer cells by inducing EMT via the Notch signaling pathway which is an autophagy‐independent mechanism. Nevertheless, Catalano et al observed that autophagy modulation triggers a molecular switch from a mesenchymal phenotype to an epithelial‐like one in glioblastoma cellular models .…”
Section: Introductionmentioning
confidence: 99%